2015
DOI: 10.3342/ceo.2015.8.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Simultaneous Application of Nonlinear Frequency Compression and Dichotic Hearing on the Speech Recognition of Severely Hearing-Impaired Subjects: Simulation Test

Abstract: ObjectivesThe clinical effects of the simultaneous application of nonlinear frequency compression and dichotic hearing on people with hearing impairments have not been evaluated previously. In this study, the clinical effects of the simultaneous application of these two techniques on the recognition of consonant-vowel-consonant (CVC) words with fricatives were evaluated using normal-hearing subjects and a hearing loss simulator operated in the severe hearing loss setting.MethodsA total of 21 normal-hearing vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…1b-d, the simulator output (solid lines) showed descending patterns similar to the applied audiograms (dashed lines). Second, we already verified the effect of variations in the smearing parameter of the simulator in a previous report, which showed that the auditory filter bandwidth of the simulator output widens as the value of the smearing parameter increases (Hwang et al 2015). To find the relevant values of the smearing parameter for each HI setup, we referred to a report of Glasberg and Moore (1986) that demonstrated that the equivalent rectangular bandwidth increased monotonically as the absolute threshold increased, as in our recent report (Hwang et al 2017).…”
Section: Synthesizing Spectral-smearing-reflected Stimulisupporting
confidence: 66%
See 1 more Smart Citation
“…1b-d, the simulator output (solid lines) showed descending patterns similar to the applied audiograms (dashed lines). Second, we already verified the effect of variations in the smearing parameter of the simulator in a previous report, which showed that the auditory filter bandwidth of the simulator output widens as the value of the smearing parameter increases (Hwang et al 2015). To find the relevant values of the smearing parameter for each HI setup, we referred to a report of Glasberg and Moore (1986) that demonstrated that the equivalent rectangular bandwidth increased monotonically as the absolute threshold increased, as in our recent report (Hwang et al 2017).…”
Section: Synthesizing Spectral-smearing-reflected Stimulisupporting
confidence: 66%
“…Although the performances of the utilized simulator in simulating deterioration in the hearing threshold and deterioration in the auditory filter bandwidth were evaluated in a verification study (Fig. 1) (Hwang et al 2015), in real-world situations, various clinical symptoms are observed in patients with sensorineural HI that are not covered by the simulator. These symptoms include loudness recruitment, dead zones, and tinnitus.…”
Section: Discussionmentioning
confidence: 99%